Population pharmacokinetics and dose evaluations of linezolid in the treatment of multidrug-resistant tuberculosis - Zhang, Haoyue; He, Yuying; Davies Forsman, Lina; Paues, Jakob; Werngren, Jim; Niward, Katarina; Schön, Thomas; Bruchfeld, Judith; Alffenaar, Jan-Willem; Hu, Yi (Frontiers in Pharmacology, 2023)
Abstract Background: The pharmacokinetic/pharmacodynamics(PK/PD) target derived from the hollow-fiber system model for linezolid for treatment of the multidrug-resistant tuberculosis(MDR-TB) requires clinical validation. Therefore, this study aimed to develop a population PK model for linezolid when administered as part of a standardized treatment regimen, to identify the PK/PD threshold associated with successful treatment outcomes and to evaluate currently recommended linezolid doses. Method: This prospective multi-center cohort study of participants with laboratory-confirmed MDR-TB was conducted in five TB designated hospitals. The population PK model for linezolid was built using nonlinear mixed-effects modeling using data from 168 participants. Boosted classification and regression tree analyses(CART) were used to identify the ratio of 0- to 24-h area under the concentration-time curve(AUC0-24h) to the minimal inhibitory concentration (MIC) threshold using the BACTEC MGIT 960 method associated with successful treatment outcome and validated in multivariate analysis using data from a different and prospective cohort of 159 participants with MDR-TB. Furthermore, based on the identified thresholds, the recommended doses were evaluated by the probability of attainment target(PTA) analysis. Result Linezolid plasma concentrations(1008 samples) from 168 subjects treated with linezolid, were best described by a 2-compartment model with first-order absorption and elimination. An AUC0–24h/MIC > 125 was identified as a threshold for successful treatment outcome. Median time to sputum culture conversion between the group with AUC0-24h/MIC above and below 125 was 2 versus 24 months; adjusted hazard ratio(aHR), 21.7; 95% confidence interval (CI),(6.4, 72.8). The boosted CART-derived threshold and its relevance to the final treatment outcome was comparable to the previously suggested target of AUC0–24h/MIC (119) using MGIT MICs in a hollow fiber infection model. Based on the threshold from the present study, at a standard linezolid dose of 600mg daily, PTA was simulated to achieve 100% at MGIT MICs of ≤ 0.25 mg which included the majority(81.1%) of isolates in the study. Conclusion: We validated an AUC0-24h/MIC threshold which may serve as a target for dose adjustment to improve efficacy of linezolid in a bedaquiline-containing treatment. Linezolid exposures with the WHO-recommended dose (600 mg daily) was sufficient for all the M. tb isolates with MIC <= 0.25 mg/L.